Building MoSe2-Mo2C incorporated hollow fluorinated carbon fibers for Li-S batteries. (15th July 2020) - Xiao, Yaoyao; Liu, Yuting; Qin, Guohui; Han, Pinyu; Guo, Xinyu; Cao, Shixun; Liu, Fusheng
Abstract: Lithium-sulfur (Li-S) batteries are severely confined by the sluggish redox kinetics and serious shuttle effect, and these disadvantages cause rapid capacity decay and low sulfur utilization efficiency. We fabricate the polar MoSe2, Mo2 C coupled with F-doped carbon fibers (FC), named as MoSe2 @FC@Mo2 C to serve as the step multi-electrocatalysts to selectively catalyze the short chain soluble lithium polysulfides (LiPSs) conversion (Li2 S4 ↔ Li2 S) via the polar FC and the long chain LiPSs conversion (S8 ↔ Li2 S4 ) via MoSe2 and Mo2 C. The MoSe2 @FC@Mo2 C/S cathode material delivered a high specific capacity of 1359 mAh g −1 (81% of its theoretical capacity) at 0.2C and excellent cycle performance when evaluated for Li-S batteries. A high reversible capacity of 802 mAh g −1 at 5C even with a lean E/S of 5 mLg −1, and a high sulfur loading of 5.5 mg cm −2 was delivered, a favorable cycle behavior at 2C over 1000 cycles (0.029% decay per cycle) was obtained, corroborating the effective LiPSs shuttling relief and high LiPSs conversion efficacy. This work propels the further practical application of Li-S batteries, especially those which are tethered by sluggish kinetics and inferior rate performance. Graphical abstract: Image 1